2015
DOI: 10.1080/07391102.2015.1044473
|View full text |Cite
|
Sign up to set email alerts
|

All-atom molecular dynamics simulations of an artificial sodium channel in a lipid bilayer: the effect of water solvation/desolvation of the sodium ion

Abstract: All-atom molecular dynamics is used to investigate the transport of Na(+) across a 1,2-dioleoyl-sn-glycero-3-phosphocholine lipid bilayer facilitated by a diazacrown hydraphile. Specifically, the free energy of Na(+) passing through the bilayer is calculated using the adaptive biasing force method to study the free energy associated with the increase in Na(+) transport in the presence of the hydraphile molecule. The results show that water interaction greatly influences Na(+) transport through the lipid bilaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Our previous work suggested that when the number of solvent states increases, there are a greater number of mechanisms that are available for transport of Na + and this could mean that the transport process is more likely. 67 (2) There is hydrogen bonding between the diazacrown oxygen and nitrogen atoms and water and this may be responsible for water ordering and channel forming in the hydraphile as proposed by Murray et al 22 The presence of Na + within the diazacrown actually strengthens the water diazacrown interaction and this may be a factor in the ordering of water. The ordering of water molecules and reduction of rotational entropy may offset this effect, however.…”
Section: Implications Of Results For Action Of Hydraphile Sodium Channelmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous work suggested that when the number of solvent states increases, there are a greater number of mechanisms that are available for transport of Na + and this could mean that the transport process is more likely. 67 (2) There is hydrogen bonding between the diazacrown oxygen and nitrogen atoms and water and this may be responsible for water ordering and channel forming in the hydraphile as proposed by Murray et al 22 The presence of Na + within the diazacrown actually strengthens the water diazacrown interaction and this may be a factor in the ordering of water. The ordering of water molecules and reduction of rotational entropy may offset this effect, however.…”
Section: Implications Of Results For Action Of Hydraphile Sodium Channelmentioning
confidence: 99%
“…The force eld used in this study was the one used in our previous work; 67 however, in that study, dihedral parameters were not included and in this case, when geometryoptimizations of the diazacrown were performed, there was a visible discrepancy between QM and force eld geometries. For this reason the dihedral parameters were added.…”
Section: Methodology/quantum Mechanical Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from controlling the drug release, the dynamics of the interfacial water should be critical for the effectiveness of the administered MSN within the body, controlling the in vivo biodistribution and bioavailability, which depend on the colloidal properties. Moreover, the interaction the MSNs with biomolecules, such as plasma proteins and lipid molecules within cell membranes, involves mediation by the structured water molecules and ions. …”
Section: Introductionmentioning
confidence: 99%
“…17 The channels that most effectively conduct alkali metal cations 14 have C n chains of 12-16 methylenes. 18,19 These bilayer-spanning amphiphiles transport Na + ions through liposomes 16 and exhibit antibacterial properties. 4 We previously reported that BC 14 H, when co-administered at sublethal concentrations, enhances the efficacy of erythromycin, kanamycin, rifampicin, and tetracycline against drug-sensitive E. coli, Pseudomonas aeruginosa, and Bacillus subtilis.…”
Section: Resultsmentioning
confidence: 99%